An introduction to forensic linguistics and forensic phonetics - Leemann, Adrian; Perkins, Ria; Buker, Grace Sullivan; Foulkes, Paul (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This textbook provides a practical introduction to the fields of forensic phonetics and forensic linguistics. Addressing how these fields are both distinct yet closely related, the book demonstrates how experts from both fields can work together to investigate and deliver justice in complex legal situations"--
Introduction to phonetic analysis -- Speaker profiling -- Speaker comparison -- Earwitness evidence -- Authentication, enhancement, and speech content determination -- Linguistic Analysis in the Asylum Procedure (LAAP).
Keywords: Forensic linguistics; Forensic phonetics; LANGUAGE ARTS & DISCIPLINES / Phonetics & Phonics